2023
DOI: 10.1097/rlu.0000000000004924
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Intrahepatic Inflammatory Myofibroblastic Tumor on 68Ga-FAPI and 18F-FDG PET/CT

Tianyue Li,
Ziliang Liu,
Zhaoqi Zhang
et al.

Abstract: A 31-year-old man with multiple intrahepatic inflammatory myofibroblastoma tumor was referred to nuclear medicine department to assess its malignant potential. Multiple lesions in the liver exhibited 68Ga-FAPI uptake at different degrees. Instead, there was no abnormal 18F-FDG activity in the other hepatic lesions under the normal liver background except for the puncture site. This case reflects tumor heterogeneity of the disease and shows the potential value of 68Ga-FAPI PET/CT for the evaluation of hepatic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Several studies have demonstrated that 68 Ga/ 18 F-FAPI PET/CT is more effective than 18 F-FDG PET/CT in detecting primary and recurrent liver cancers, including hepatocellular carcinoma, 4-6 intrahepatic cholangiocarcinoma, 5,6 mucosa-associated lymphoid tissue, 7 liver metastases, 8,9 and some benign liver diseases. 6,[10][11][12] In our case, significant 18 F-FAPI uptake was observed, suggesting that 18…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Several studies have demonstrated that 68 Ga/ 18 F-FAPI PET/CT is more effective than 18 F-FDG PET/CT in detecting primary and recurrent liver cancers, including hepatocellular carcinoma, 4-6 intrahepatic cholangiocarcinoma, 5,6 mucosa-associated lymphoid tissue, 7 liver metastases, 8,9 and some benign liver diseases. 6,[10][11][12] In our case, significant 18 F-FAPI uptake was observed, suggesting that 18…”
mentioning
confidence: 52%
“…But in our case, the small recurrent cHCC-CC lesion demonstrated a low level of 18 F-FDG uptake, leading to a false-negative 18 F-FDG PET/CT result. Several studies have demonstrated that 68 Ga/ 18 F-FAPI PET/CT is more effective than 18 F-FDG PET/CT in detecting primary and recurrent liver cancers, including hepatocellular carcinoma, 4–6 intrahepatic cholangiocarcinoma, 5,6 mucosa-associated lymphoid tissue, 7 liver metastases, 8,9 and some benign liver diseases 6,10–12 . In our case, significant 18 F-FAPI uptake was observed, suggesting that 18 F-FAPI PET/CT may be a promising imaging procedure in the management of cHCC-CC.…”
mentioning
confidence: 52%